A Swedish translation and validation of the Mother-to-Infant Bonding Scale. Issue 4 (June 2021) - Mörelius, Evalotte; Elander, Anna; Saghamre, Emmy
Aim: This study aimed to test initial validity, reliability, and feasibility of the Mother-to-Infant Bonding Scale in a sample of Swedish mothers. Methods: A translation was performed through 11 steps using a forward–backward bilingual technique. For criterion validity, the Swedish translation of the Mother-to-Infant Bonding Scale (S-MIBS) was compared with the Postpartum Bonding Questionnaire, sub-scale 1 (PBQ1) and 2 (PBQ2) and Edinburgh Postnatal Depression Scale (EPDS) in a sample of 63 Swedish mothers. Internal consistency was calculated with Cronbach's alpha. For feasibility testing, the mothers were asked to grade their experience of S-MIBS and PBQ on a four-point scale. Results: The results show a correlation between S-MIBS and PBQ1 ( r =0.80, p <0.001), PBQ2 ( r =0.69, p <0.001) and EPDS ( r =0.44, p <0.001). Internal consistency was α=0.68. Most mothers (93.1%) found S-MIBS to be easy or very easy to complete compared with PBQ (88.7%). Conclusions: The initial testing of the Swedish translation of the Mother-to-Infant Bonding Scale shows usability to measure the mother's emotions towards her healthy full-term infant.